2021
DOI: 10.1155/2021/6611407
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Service-Oriented Architecture and Scrum Software Development Approach for IIoT

Abstract: Flexibility and change adoption are key attributes for service-oriented architecture (SOA) and agile software development processes. Although the notion of agility is quite visible on both sides, still the integration of the two diverse concepts (architectural framework and development process) should be well thought of before employing them for a software development project. For this purpose, this study is designed to analyze the two diverse software architectural framework and development approaches, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The research study published in 2014 by Dave Murry-Rust et al [19] state that crowdsourcing systems are primarily used for simple task with simple integration. Crowdsource platforms provide limited assistance in dealing with organisational challenges, and intellectual and complex labour types like software development [20]. To support crowdsourcing of the software development the system needs to implement the mechanism to integrate human activity and creativity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research study published in 2014 by Dave Murry-Rust et al [19] state that crowdsourcing systems are primarily used for simple task with simple integration. Crowdsource platforms provide limited assistance in dealing with organisational challenges, and intellectual and complex labour types like software development [20]. To support crowdsourcing of the software development the system needs to implement the mechanism to integrate human activity and creativity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, using the SCRUM process paradigm to develop software involves increasing organizational agility by combining SCRUM principles that can improve collaboration, communication, and feedback [13,14]. Although there are some similarities and incompatibilities between SCRUM and SOA, as previously noted, there are certain distinctions and incompatibilities between the two techniques To design a framework for their integration, the compatibility and commonality of these two development approaches are investigated [50,51].…”
Section: Scrum and Soa Compatibility Discussionmentioning
confidence: 99%
“…The idea of using a case is part of a research strategy, as indicated by the Saunders et al research onion [24]. Case studies may be categorized into three categories: explanatory, exploratory, and descriptive [25]. Since we are investigating an Agile-FMs interplay, our case study is exploratory.…”
Section: Are Formal Methods Ready For Agile?mentioning
confidence: 99%